Stakeholders' views on volunteering in mental health: an international focus group study. Issue 3 (17th March 2022) - Pinto da Costa, Mariana; Conneely, Maev; Monteiro da Silva, Fábio; Toner, Sarah
Abstract : Objectives: Explore the views of two main stakeholders: mental health professionals and volunteers from three European countries, on the provision of volunteering in mental healthcare. Design: A multicountry, multilingual and multicultural qualitative focus group study (n=24) with n=119 participants. Participants: Volunteers and mental health professionals in three European countries (Belgium, Portugal and the UK). Results: Mental health professionals and volunteers consider it beneficial offering volunteering to their patients. In this study, six overarching themes arose: (1) there is a framework in which volunteering is organised, (2) the role of the volunteer is multifaceted, (3) every volunteering relationship has a different character, (4) to volunteer is to face challenges, (5) technology has potential in volunteering and (6) volunteering impacts us all. The variability of their views suggests a need for flexibility and innovation in the design and models of the programmes offered. Conclusions: Volunteering is not one single entity and is strongly connected to the cultural context and the mental healthcare services organisation. Despite the contextual differences between these three European countries, this study found extensive commonalities in attitudes towards volunteering in mental health.